EFFECT OF ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION THROUGH BRAND IMAGE AS MEDIA IN TOKOPEDIA - Natasha Theodora Handoko; Tina Melinda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to acknowledge the effect of Electric Word of Mouth in giving impact for consumer purchase interest which is mediated by Brand image in Tokopedia. Sampling extractions which are conducted using purposive sampling method, categorized by age above 15 years old participants. And for those who have experienced with Tokopedia before. The collective data is gathered from 5 big cities in Indonesia which are Jakarta, Surabaya, Yogyakarta, Semarang and Most by. spreading questionnaires to the customers who used Tokopedia. There are 100 customers representative. This data processing is conducted with the Convergent Validity Test, Discrimination Validity Test, Reliability Test with Cronbach's Alpha and Composite Reliability, Path Coefficient, R Square, F- Square and Sobel Test which are processed by Partial Least Square (PLS). From the result of these tests, I can conclude that Electric Word of Mouth has a significant impact to the consumers purchase interest and has a significant impact to the Brand image. Whilst the Brand image has a significant impact to the purchase interest. This research outcome also depicts that Electric Mouth has a direct impact to the purchase interest which is mediated by the Brand image Keywords: Electronic Word Of Mouth, Brand Image, Purchase Intention